From student feedback to institutional quality enhancement initiatives that focus on supporting staff and students - Santhanam, Elizabeth; Ashford-Rowe, Kevin; Murphy, Pauline (Critical Studies in Teaching and Learning, 2023)
The broader  challenges  posed  for  teaching  quality  enhancement  through  educational  and academic  development  are  many  and  include:  information  collection  to  identify  possible reasons  for  a  particular  set  of  circumstances,  planning  and  implementation  of  changes  in  a generally  fluid  situation,  collection  of  evidence  for  outcomes, and  provision  of  succinct reports to stakeholders. One common means for identifying both the needs and the outcomes is through surveys. In this respect, students views on the learning and teaching environment provided by an institution are typically collected through standardised questionnaires, though the use of such survey  results  has  been  frequently  debated.  This paper outlines  the  use  of information collected through surveys of student views in order to better understand student learning experiences and to identify areas for further development. It also describes specific projects and programs  that  were  aimed  at  caring  for  both  staff  and  students  in  an  institution with a  strong  commitment  to  the dignity  of  the  human  person and  the common  good.  It is noted that in  addition  to  policies  and  procedures  that  enshrine  caring  and  ethical  behaviour among  staff  and  students,  the  institution  actively  promotes  this  culture  through  various practices.